2003
DOI: 10.1046/j.1462-2920.2003.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal diversity associated with in situ samplers deployed on hydrothermal vents on the East Pacific Rise (13°N)

Abstract: To evaluate possible compositional changes in archaeal communities at a deep-sea hydrothermal vent field scale, we examined five different samples obtained after deploying in situ collectors for different times on three spatially separated venting sulphide structures on the East Pacific Rise (13 degrees N). Direct cell counts and whole-cell hybridizations with fluorescently labelled 16S rRNA-based oligonucleotide probes revealed that the relative abundance of archaeal populations represented from 14 to 33% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 34 publications
2
111
0
Order By: Relevance
“…Because previous work has 373 indicated that uncultured crenarchaea dominate the interior of sulfide structures (Schrenk 374 et al 2003), we conducted global sequence comparisons of the Hulk high-temperature 375 v4-v6 region against a database of uncultured crenarchaea identified from sulfide clone 376 libraries. Two sequences were found that matched previously identified crenarchaea in 377 sulfides at 99-100% identity: a Desulfurococcales lineage from a white smoker spire on 378 the East Pacific Rise (Kormas et al 2006), and a Pyrodictium lineage identified in an in-379 situ growth chamber deployed within a sulfide structure (Nercessian et al 2003). 380 381 Discussion 382…”
Section: Persistence Of Otus Across Samples 331mentioning
confidence: 62%
“…Because previous work has 373 indicated that uncultured crenarchaea dominate the interior of sulfide structures (Schrenk 374 et al 2003), we conducted global sequence comparisons of the Hulk high-temperature 375 v4-v6 region against a database of uncultured crenarchaea identified from sulfide clone 376 libraries. Two sequences were found that matched previously identified crenarchaea in 377 sulfides at 99-100% identity: a Desulfurococcales lineage from a white smoker spire on 378 the East Pacific Rise (Kormas et al 2006), and a Pyrodictium lineage identified in an in-379 situ growth chamber deployed within a sulfide structure (Nercessian et al 2003). 380 381 Discussion 382…”
Section: Persistence Of Otus Across Samples 331mentioning
confidence: 62%
“…Samples were collected from two sites on the East Pacific Rise, 9°50′N, 104°17′W by Deep Submergence Vehicle Alvin, and 13°N (12°49′N, 103°56′W) at a depth of 2,500 m by Deep Submergence Vehicle Nautile. Further description of sampling procedures and isolation sites has been described elsewhere (68). Samples were inoculated into heterotrophic, anaerobic seawater-based media immediately after sample retrieval onboard the mother ship.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic characteristics of these communities might be analogous to those that inhabit deep-ocean hydrothermal systems today (e.g. Nercessian et al 2003;Alain et al 2004). As there is no fresh crater available for study, the true nature of the hydrothermal microbial ecosystems that inhabited early Archaean craters must be subject to some conjecture, but if the earliest life forms were hyperthermophilic, perhaps owing to an evolutionary bottleneck, then impacts would not only have caused this bottleneck, but also would have generated hot conditions that favoured colonization by the microorganisms that survived the previous impacts.…”
Section: Craters As Habitats For Early Lifementioning
confidence: 99%